2002
DOI: 10.1266/ggs.77.117
|View full text |Cite
|
Sign up to set email alerts
|

A new mutation of the ATP-binding cassette, sub-family C, member 2 (ABCC2) gene in a Japanese patient with Dubin-Johnson syndrome.

Abstract: Dubin-Johnson syndrome (DJS) is an inherited disorder characterized by conjugated hyperbilirubinemia and is caused by mutations of the canalicular multispecific organic anion transporter (cMOAT)/ multidrug resistance protein 2 (MRP2)/ ATP-binding cassette, sub-family C, member 2 (ABCC2) gene. The ABCC2 protein is located in the apical membrane of hepatocytes, and known mutations of this gene cause impaired maturation and trafficking of the mutated protein from the endoplasmic reticulum (ER) to the Golgi comple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 24 publications
(26 reference statements)
0
10
0
Order By: Relevance
“…The mutations are different from those reported from Japanese patients. Most reported mutations of the ABCC2 gene in DJS involve one or both ABC (8). These ABC are important for ATP binding and are highly conserved (7,8).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The mutations are different from those reported from Japanese patients. Most reported mutations of the ABCC2 gene in DJS involve one or both ABC (8). These ABC are important for ATP binding and are highly conserved (7,8).…”
Section: Discussionmentioning
confidence: 99%
“…Most reported mutations of the ABCC2 gene in DJS involve one or both ABC (8). These ABC are important for ATP binding and are highly conserved (7,8). From reviewing reported cases, almost all the patients diagnosed as DJS before 10 y of age have mutations involving one of the two ABC of the MRP2 protein whereas mutations involving domains other than ABC of the MRP2 protein are observed mostly in adults (see Table 2).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various polymorphisms in the MRP2 gene contribute to the etiology of the Dubin-Johnson syndrome (Paulusma et al, 1996;Wada et al, 1998;Tsujii et al, 1999;Mor-Cohen et al, 2001;Tate et al, 2002;Materna and Lage, 2003;Wakusawa et al, 2003). It was shown that single nucleotide changes like the 3517 A/T transition in exon 25 are associated with lower efflux of MRP2 substrates and altered distribution of the protein in transfected cells (Mor-Cohen et al, 2001;Keitel et al, 2003).…”
Section: Meyer Zu Schwabedissen Et Almentioning
confidence: 99%